2021
DOI: 10.1111/hsc.13318
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of willingness to care for people living with HIV‐AIDS: A cross‐sectional study in Indonesia

Abstract: The acceptance of people living with HIV-AIDS (PLHA) within the community is still a problem that should be highlighted and addressed (Fitriyani & Waluyo, 2019). Bringing attention to this problem could also have an impact on the community's willingness to help and care for PLHA (Stroumpouki et al., 2020). The operational definition of caring, in this case, not only refers to caring for PLHA who are sick but also to being willing to provide the support, attention, information, assistance and acceptance that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
(45 reference statements)
2
12
0
2
Order By: Relevance
“…The global screening of pregnant women is essential to prevent the mother-to-child transmission (MTCT) of HIV through provider-initiated routine testing and antiretroviral therapy (ART) in antenatal clinics [ 10 , 42 , 43 ]. In line with the previous studies, the results reported that women had a higher percentage of undergoing HIV tests in the last 12 months in five out of sixteen countries [ 40 , 44 ]. However, many women have still not yet been tested for HIV/AIDS [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…The global screening of pregnant women is essential to prevent the mother-to-child transmission (MTCT) of HIV through provider-initiated routine testing and antiretroviral therapy (ART) in antenatal clinics [ 10 , 42 , 43 ]. In line with the previous studies, the results reported that women had a higher percentage of undergoing HIV tests in the last 12 months in five out of sixteen countries [ 40 , 44 ]. However, many women have still not yet been tested for HIV/AIDS [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…Good knowledge of HIV must also be possessed by the community and the individual's family. This can have an impact on the acceptance of people living with HIV (PLWH) in the community, as well as combating low stigma and discrimination [27]. Therefore, knowledge is important when it comes to preventing HIV transmission and combating stigma and discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Coping strategies can be defined as an individual's efforts to use cognitive and behavioral strategies to manage and regulate pressures, demands, and emotions in response to stress. People can develop either emotion or problem-focused coping (PFC) strategies [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%